2020
DOI: 10.1101/2020.04.07.029595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The histone variant H2A.Z is required to establish normal patterns of H3K27 methylation inNeurospora crassa

Abstract: 25 Neurospora crassa contains a minimal Polycomb repression system, which provides rich 26 opportunities to explore Polycomb-mediated repression across eukaryotes and enables genetic 27 studies that can be difficult in plant and animal systems. Polycomb Repressive Complex 2 is a 28 multi-subunit complex that deposits mono-, di-, and tri-methyl groups on lysine 27 of histone 29 H3, and tri-methyl H3K27 is a molecular marker of transcriptionally repressed facultative 30 heterochromatin. In mouse embryonic stem c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Moreover, H2A.Z appears to colocalize with H3K27 methylation in plants and animals [5,73]. It was recently demonstrated that in N. crassa H2A.Z and the CRF, SWR-1, similarly promote H3K27 methylation, although H2A.Z and H3K27 methylation were not found to colocalize [74].…”
Section: Defining the Minimal H3k27me3 Network: Fungi As Excellent Gementioning
confidence: 99%
“…Moreover, H2A.Z appears to colocalize with H3K27 methylation in plants and animals [5,73]. It was recently demonstrated that in N. crassa H2A.Z and the CRF, SWR-1, similarly promote H3K27 methylation, although H2A.Z and H3K27 methylation were not found to colocalize [74].…”
Section: Defining the Minimal H3k27me3 Network: Fungi As Excellent Gementioning
confidence: 99%
“…In filamentous fungi, the histone code was initially studied in the saprophyte Neurospora crassa [14,15]. In this species, histone modifications affect transcription, DNA replication, DNA repair, and chromosome segregation [14,[16][17][18][19][20][21]. The impact of histone modifications have been studied in other filamentous fungi, including saprophytes as well as human pathogens, such as Aspergillus species [22,23], and in various plant pathogens [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%